MicroRNA expression as predictor of local recurrence risk in oral squamous cell carcinoma. (24th June 2015) - Ganci, Federica; Sacconi, Andrea; Manciocco, Valentina; Sperduti, Isabella; Battaglia, Paolo; Covello, Renato; Muti, Paola; Strano, Sabrina; Spriano, Giuseppe; Fontemaggi, Giulia; Blandino, Giovanni
ABSTRACT: Background: Oral squamous cell carcinoma (OSCC) is the sixth most common cancer worldwide with a high rate of recurrence. MicroRNAs (miRNAs) are gene regulators playing an important role in oral carcinogenesis. The purpose of this study was for us to identify and functionally characterize miRNAs that predict recurrence in OSCC. Methods: We collected 92 OSCC with their normal tissue counterparts and we performed miRNAs expression profiling on 74 OSCC and 38 normal tissues. The association between the expression of miRNAs and clinical outcome was evaluated in the follow‐up of 69 patients. Results: Four of the miRNAs deregulated between OSCC and normal tissues are prognostic for recurrence either when considered individually or as a group. Depletion of the expression of prognostic miRNAs inhibit the proliferation of OSCC cells Conclusion: MiRNAs are differentially expressed in OSCC versus normal samples. The expression of 4 prognostic miRNA signatures is able to predict recurrence risk independently from other clinical factors in OSCC. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E189–E197, 2016